2015
DOI: 10.3390/molecules201219773
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Stable Primary-Alkyl-Substituted Selenenyl Iodide and Its Hydrolytic Conversion to the Corresponding Selenenic Acid

Abstract: Abstract:A primary-alkyl-substituted selenenyl iodide was successfully synthesized through oxidative iodination of a selenol with N-iodosuccinimide by taking advantage of a cavity-shaped steric protection group. The selenenyl iodide exhibited high thermal stability and remained unchanged upon heating at 100˝C for 3 h in [D 8 ]toluene. The selenenyl iodide was reduced to the corresponding selenol by treatment with dithiothreitol. Hydrolysis of the selenenyl iodide under alkaline conditions afforded the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, selenenic acids generated during the oxidation of selenols readily form diselenides by the reaction with unreacted selenols . Our and other groups have reported on the observation and isolation of nonselenocysteinyl-derivative selenenic acids by either kinetic or thermodynamic stabilization techniques. However, these nonselenocysteinyl derivatives do not adequately reproduce the characteristic reactivity of Sec–SeOH in proteins.…”
mentioning
confidence: 95%
“…Furthermore, selenenic acids generated during the oxidation of selenols readily form diselenides by the reaction with unreacted selenols . Our and other groups have reported on the observation and isolation of nonselenocysteinyl-derivative selenenic acids by either kinetic or thermodynamic stabilization techniques. However, these nonselenocysteinyl derivatives do not adequately reproduce the characteristic reactivity of Sec–SeOH in proteins.…”
mentioning
confidence: 95%
“…However, the steric demands of usual primary-alkyl groups are too small to protect such reactive species, and there has been no example of the synthesis of a thionitrate bearing a primary-alkyl group. Meanwhile, we have recently developed an effective primary-alkyl steric protection group, a BpqCH 2 group ( Figure 1 ), with a cavity-shaped framework and succeeded in the isolation of reactive species such as a sulfenic acid [ 18 ], a sulfenyl iodide [ 19 ], a selenenic acid [ 20 ], and a selenenyl iodide [ 21 ] by utilizing this substituent. Thus, a model study by utilizing the BpqCH 2 group was examined.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our studies on biologically relevant highly reactive species containing sulfur and selenium, we have developed various cavity-shaped substituents and demonstrated that these substituents are very effective for kinetic stabilization of highly reactive species that otherwise undergo facile bimolecular decomposition [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Herein, we report a model study on the bioactivation of an organic nitrate by a thiol, which is the fundamental chemical process in the thiol-dependent biotransformation of nitrates.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the truncated catalytic domain of mouse Dio3 has been solved [ 256 ], and it shows that the enzyme has a close structural similarity to atypical 2-Cys peroxiredoxins. The structure is compatible with Sec170 extracting the 5-iodine as a selenenyl-iodide, which should then hydrolyze to a selenenic acid intermediate, as supported by model studies with a synthetic alkylselenenyl-iodide [ 262 ]. It also shows that the thyronine ring is protonated via a network of conserved amino acids.…”
Section: Mammalian Selenoproteinsmentioning
confidence: 92%